PENGARUH BUDAYA ORGANISASI CINA DAN KOMPENSASI TERHADAP KINERJA PADA BEBERAPA BADAN USAHA DI LAMPUNG - Andy Fitriyadi Dharma Tilaar (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2016)
One of theory that become a background of this research is performance that influenced bythe Chinese culture organization and compensation. This problem is being attractive since manybusiness competitions have been won by Chinese descent. It makes a negative polemic; polemicthat caused by business style and tricks which sometimes unreasonable but happened.Chinese culture organization is not a theory that having the real quality but uniqueness, itcaused by the increasing performance not only because of compensation but also awareness ofrelation and cooperation. This is proven by the number of Chinese cultural organization relationeffect and the compensation on performance as 89.6 %, this is confirmed by the number of theChinese cultural organization constant effect as 1.457 towards others free variable that is 0.337.